Highly Immersive Programme (HIP): the challenges faced by ESL teachers in rural schools - Mohamad, Maslawati; Adnan, Erra Farina; Alias, Bity Salwana; Mohd Zahidi, Azizah; Md Zamin, Ainul Azmin; Kamarudin, Rafidah (IJLTER, 2025)
The Highly Immersive Programme (HIP) is an initiative introduced by the Ministry of Education Malaysia (MOE) to enhance pupils’ English language proficiency. Implemented under the Malaysia Education Blueprint (2013–2025), HIP promotes language acquisition through immersive activities and increased exposure to English in both formal and informal settings. This qualitative study explores the challenges faced by ESL teachers in implementing HIP in rural Malaysian schools. Employing a multiple case study design, the research involved semi-structured focus group interviews with 15 ESL teachers across five rural schools. Additional data collection methods included responses via Google Forms and photographic documentation of HIP activities. Findings indicate that ESL teachers encounter several critical challenges, including limited teaching resources, low parental involvement, students' limited English proficiency, and the burden of planning and executing HIP activities amidst an already demanding workload. These challenges significantly impede the programme’s effectiveness in improving pupils’ English skills. The study highlights the need for comprehensive support for teachers, such as increased resource allocation, initiatives to foster parental engagement, and measures to reduce teacher workload. Effective collaboration among school administrators, teachers, parents, and community stakeholders is essential to overcoming these barriers and ensuring the successful implementation of HIP